Effect of teduglutide, a glucagon-like peptide-2 analog, in eosinophilic enterocolitis: a case report - Ogawa, Shoko; Konishi, Ken-ichiro; Tanaka, Kiyoshi; Takayasu, Hajime; Uematsu, Yoshimasa; Ito, Takashi; Takahashi, Hiroyuki; Kumamoto, Yusuke (Frontiers in Pediatrics, 2024)
We successfully treated a 4-year-old girl with short bowel syndrome and eosinophilic enterocolitis with teduglutide, a glucagon-like peptide-2 analog. Her eosinophilic enterocolitis was cured without relapse, and we were able to increase enteral nutrition. We found that teduglutide had an antiinflammatory effect in this patient with eosinophilic gastrointestinal disease associated with short bowel syndrome. This report is the first to describe use of teduglutide in the treatment of eosinophilic gastrointestinal disease.